3
$\begingroup$

In particular, when $x=y=z$ isn't the above expression equal to 1 and not -1?

$\endgroup$
  • 1
    $\begingroup$ try reading the above as "a change in x due to a change in y divided by a change in y times a change in y due to a change in z divided by a change in z times a change in z due to a change in x divided by a change in x". Notice that, for example, that "a change in y due to a change in z" and "a change in y" do not represent the same quantity. $\endgroup$ – John Joy Sep 23 '14 at 14:06
  • $\begingroup$ I'll have to think about it more, thanks. $\endgroup$ – user174513 Sep 24 '14 at 6:19
3
$\begingroup$

I'm afraid that your comment about letting $x=y=z$ makes no sense at all here.

The formula ("Barkhausen's tube formula") concerns the situation when there are three quantities $x$, $y$ and $z$ constrained by a relation $F(x,y,z)=0$, so that one can view either one of them as a function of the two others: $x=x(y,z)$ or $y=y(x,z)$ or $z=z(x,y)$.

(At least this holds locally near some point $(x,y,z)=(a,b,c)$ such that $F(a,b,c)=0$, provided that the partial derivatives $F'_x$, $F'_y$ and $F'_z$ all are nonzero at this point, and $F$ is of class $C^1$; this is the implicit function theorem.)

To avoid confusion, write $x=f(y,z)$, $y=g(x,z)$ and $z=h(x,y)$ instead. Then instead of $\partial x/\partial y$ we write $f'_y$, and in particular at the point $(x,y,z)=(a,b,c)$ we write $f'_y(b,c)$, etc. Implicit differentiation shows that $$ \left( \frac{\partial x}{\partial y} = \right)\quad f'_y(b,c)=- \frac{F'_y(a,b,c)}{F_x'(a,b,c)} , $$ $$ \left( \frac{\partial y}{\partial z} = \right)\quad g'_z(a,c)=- \frac{F'_z(a,b,c)}{F_y'(a,b,c)} , $$ $$ \left( \frac{\partial z}{\partial x} = \right)\quad h'_x(a,b)=- \frac{F'_x(a,b,c)}{F_z'(a,b,c)} . $$ The product of these expressions is $-1$, and that's your formula.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy